A Complex Self‐Catenated Coordination Framework with a Rare (3, 12)‐Connected Underlying Net Showing Selective Adsorption of CO2. Issue 28 (31st August 2015) - Luo, Feng; Meng, Pan Pan; Feng, Xue Feng; Dang, Li Long; Zhang, Xiao Jing
Abstract: Herein, we report a unique self‐catenated metal‐organic framework (MOF) with an underlying (3, 12)‐connected topology based on Co4 clusters. Moreover, the special dumbbell‐like pore configuration, the exact match between the pore aperture and the kinetic diameter of CO2, as well as the coexistence of acylamide and NH2 groups in the MOF enhances the selectivity of adsorption of CO2 over other gases such as CO, CH4, O2, and N2 . Abstract : We report a complex self‐catenated MOF showing a highly rare (3, 12)‐connecting underlying net built on a 12‐connecting Co4 node and a 3‐connecting ligand node. This MOF is the first that features a (3, 12)‐connecting net and self‐catenation.